High-toughness nodular cast iron and method for producing the same

CN122484605BActive Publication Date: 2026-10-23TAIYUAN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610944517.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-23
Estimated Expiration
2046-06-29

AI Technical Summary

Technical Problem

热处理(如调制处理、退火)虽能显著改善材料性能,但生产周期长,易导致氧化、变形或开裂,增加废品率与能耗

Benefits of technology

[0022]本发明通过熔炼阶段直接加入铌铁实现铌的合金化,工艺简便,成本更低。铌元素在凝固及后续共析转变过程中,与碳结合生成纳米级NbC颗粒,在珠光体基体中弥散析出,通过钉扎位错及细化珠光体片层间距,产生强烈的沉淀强化效果,从而显著提高材料的强度、硬度、耐磨性及高温稳定性。通过严格控制原铁水的低硫、低氧状态,为铌元素的充分溶解及碳化铌的有效生成创造了良好的冶金条件。采用包芯线喂丝法进行球化处理,镁吸收率高且稳定,球化过程烟尘少、环境友好,同时配合精确控制的稀土球化剂及合理的镁、稀土残留窗口,避免了过量稀土对石墨形态的恶化。结合低温浇铸与针对厚壁部位的加速冷却工艺,促进碳化物在凝固初期弥散析出并有效抑制其高温粗化,实现了石墨形态调控与基体强化的协同。采用本方法制备的球墨铸铁具备良好的综合力学性能,兼具高强度与高塑性,能够胜任汽车桥壳等领域中对强韧性有着严苛要求的高负荷结构件的应用需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122484605B_ABST
    Figure CN122484605B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of metal materials, and particularly relates to high-strength and high-toughness nodular cast iron and a preparation method thereof, wherein the preparation method comprises the following steps: S1, obtaining raw materials and carrying out smelting to obtain an iron liquid, adding ferro-niobium in the smelting process, heating the iron liquid to 1540-1610 DEG C and keeping the temperature for 5-15 min; S2, carrying out desulfurization and deoxidation treatment on the iron liquid, and tapping the iron liquid after slagging, wherein the temperature of the tapped iron liquid is 1480-1520 DEG C; S3, adding rare earth spheroidizing agent and primary inoculant into the iron liquid after slagging to obtain a metal liquid; and S4, pouring the metal liquid, adding secondary inoculant in the pouring process, and obtaining the high-strength and high-toughness nodular cast iron after cooling. In the application, the alloying of niobium is realized by directly adding ferro-niobium in the smelting stage, the process is simple, the spheroidizing process is accurately controlled by using the wire feeding method, the prepared nodular cast iron has high strength and high plasticity, has excellent comprehensive mechanical properties, and can meet the application requirements of high-load structural parts with strict requirements on strength and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal materials technology, specifically a high-strength and high-toughness ductile iron and its preparation method. Background Technology

[0002] Ductile iron, through spheroidization and inoculation treatment, transforms graphite into a spherical shape, minimizing its cutting effect on the matrix. This material combines high strength, high toughness, excellent wear and corrosion resistance, and good casting properties, making it suitable for high-load operating conditions. In the automotive industry, the drive axle housing is a critical safety component that bears the weight of the vehicle body, transmits driving force, and withstands complex alternating loads. Using ductile iron integrally cast axle housing can reduce the number of parts, simplify assembly processes, and lower manufacturing costs, while utilizing the inherent vibration damping properties of cast iron to improve ride comfort. Currently, grades such as QT450-10, QT500-7, and QT600-3 are widely used in medium and heavy-duty commercial vehicle axle housings. However, as the automotive industry rapidly develops towards higher power density, lighter weight, and longer service life, the service conditions of axle housings are becoming increasingly demanding, placing higher requirements on the strength and toughness of the materials. The performance of existing ductile iron grades is gradually reaching its limits: high-strength grades (such as QT700-2) often lack sufficient plasticity (elongation ≤2%), making them prone to brittle fracture; while high-plasticity grades (such as QT500-7) have limited strength reserves, making it difficult to meet the load-bearing requirements of lightweight and thinner designs. Therefore, developing new types of ductile iron that combine high strength (tensile strength ≥700MPa) and good plasticity (elongation ≥10%) has become an urgent need for upgrading automotive axle housing materials.

[0003] To improve the overall mechanical properties of ductile iron, researchers both domestically and internationally have mainly explored three directions: heat treatment, composite casting, and alloying. While heat treatment (such as tempering and annealing) can significantly improve material properties, it has a long production cycle and is prone to oxidation, deformation, or cracking, increasing scrap rates and energy consumption. Especially for large and complex castings like bridge housings, controlling dimensional stability after heat treatment is difficult, further increasing manufacturing costs. Composite casting (such as adding micro / nano particles) can refine the microstructure to some extent, but the particles have poor wettability with molten iron, are prone to agglomeration and floating, and suffer from insufficient process stability. Alloying is a more direct and effective approach; however, there is often a trade-off between elements: increasing the content of Cu, Mn, and Mo can strengthen the pearlite matrix but sacrifices plasticity; excessive rare earth elements or magnesium residues may induce graphite distortion. Therefore, it is urgent to explore a novel alloying strategy that can effectively refine graphite spheroids while simultaneously strengthening the matrix without significantly impairing plasticity. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a method for preparing high-strength and high-toughness ductile iron, comprising the following steps:

[0005] S1. Obtain raw materials and smelt them to obtain molten iron. During the smelting process, add ferroniobium and heat the molten iron to 1540~1610℃ and keep it at that temperature for 5~15 minutes.

[0006] S2. The molten iron is subjected to desulfurization and deoxidation treatment, and the slag is removed before iron is discharged. The temperature of the discharged iron is 1480~1520℃.

[0007] S3. Add rare earth spheroidizing agent and primary inoculant to the molten iron after slag removal to obtain molten metal.

[0008] S4. The molten metal is poured, and a secondary inoculant is added during the pouring process. After cooling, the high-strength and high-toughness ductile iron is obtained.

[0009] The chemical composition of the high-strength and high-toughness ductile iron includes: C 3.2wt%~3.8wt%, Mg 0.03wt%~0.05wt%, Nb 0.07wt%~0.09wt%, RE≤0.04wt%, S≤0.015wt%;

[0010] The ductile iron has a tensile strength greater than or equal to 700 MPa, a yield strength greater than or equal to 540 MPa, a hardness greater than or equal to 240 HB, and an elongation greater than or equal to 10%.

[0011] In step S2, the sulfur content in the molten iron after desulfurization and deoxidation treatment is ≤0.02wt%, and the oxygen content is ≤20ppm.

[0012] The rare earth spheroidizing agent and the primary inoculant are added using a cored wire feeding method;

[0013] In step S4, the temperature at which the molten metal is poured is 1360~1380℃;

[0014] In step S4, the cooling specifically involves accelerating the cooling of the thick-walled portion during the solidification of the ductile iron. The thick-walled portion is the casting portion with a wall thickness greater than or equal to 50 mm. The accelerated cooling involves placing an external chill at the hot spot or using air cooling to make the cooling rate of the eutectoid transformation zone greater than or equal to 50 °C / min.

[0015] In step S1, the raw materials include at least one of Q10 pig iron, scrap steel, and recycled materials.

[0016] In step S1, the ferroniobium is an FeNb60 alloy, and the amount of ferroniobium added is 0.12% to 0.2% of the total mass of the molten iron.

[0017] In step S3, the primary inoculant includes barium silicon inoculant, ferrosilicon inoculant, or calcium silicon inoculant; the amount of rare earth spheroidizing agent added is 1% to 1.5% of the total mass of the molten iron, and the amount of primary inoculant added is 0.2% to 0.27% of the total mass of the molten iron.

[0018] In step S3, the rare earth content in the rare earth spheroidizing agent is ≤2wt%, the residual magnesium content in the molten metal is 0.035wt%~0.050wt%, and the residual rare earth content is 0.010wt%~0.030wt%.

[0019] In step S4, the secondary inoculant includes barium silicon inoculant, ferrosilicon inoculant, or calcium silicon inoculant, and the amount added is 0.1% to 0.13% of the total mass of the molten iron.

[0020] To address the aforementioned technical problems, this invention also provides a high-strength and high-toughness ductile iron, prepared using the above-described method. The chemical composition of the ductile iron, by mass percentage, includes: C 3.2wt%~3.8wt%, Si 2.3wt%~3.5wt%, Mn 0.1wt%~0.7wt%, Cu 0.3wt%~0.9wt%, Sn 0.03wt%~0.035wt%, Mg 0.03wt%~0.05wt%, Ni 0.3wt%~0.5wt%, Nb 0.07wt%~0.09wt%, RE≤0.04wt%, Ti 0.02wt%~0.04wt%, P≤0.03wt%, S≤0.015wt%, Al 0.01wt%~0.02wt%, Cr<0.1wt%, B<0.001wt%, with the balance being Fe and unavoidable impurities.

[0021] Furthermore, the spheroidization rate of the ductile iron is greater than or equal to 92%, wherein the number of graphite spheres is greater than or equal to 250 per mm. 2 The content of pearlite is greater than or equal to 70%, and the content of ferrite is less than or equal to 30%.

[0022] This invention achieves niobium alloying by directly adding ferroniobium during the smelting stage, resulting in a simpler and lower-cost process. During solidification and subsequent eutectoid transformation, niobium combines with carbon to form nano-sized NbC particles, which are dispersed and precipitated in the pearlite matrix. This precipitation strengthens the material by pinning dislocations and refining the interlamellar spacing, significantly improving its strength, hardness, wear resistance, and high-temperature stability. Strict control of the low-sulfur and low-oxygen conditions of the molten iron creates favorable metallurgical conditions for the complete dissolution of niobium and the effective formation of niobium carbide. The spheroidizing process uses a cored wire feeding method, which offers high and stable magnesium absorption. The process produces less dust and is environmentally friendly. Furthermore, precise control of rare earth spheroidizing agents and a reasonable magnesium and rare earth residue window prevents excessive rare earth from deteriorating the graphite morphology. Combining low-temperature casting with accelerated cooling for thick-walled sections promotes the dispersed precipitation of carbides in the early stages of solidification and effectively inhibits their high-temperature coarsening, achieving a synergistic effect of graphite morphology control and matrix strengthening. The ductile iron prepared by this method has good comprehensive mechanical properties, combining high strength and high plasticity, and can meet the application requirements of high-load structural components in fields such as automotive axle housings where stringent requirements for strength and toughness are placed. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0024] Figure 1 This is a spheroidization rate rating chart for the ductile iron prepared in Example 1 of the present invention;

[0025] Figure 2 This is a spheroidization rate rating chart for the ductile iron prepared in Example 2 of the present invention;

[0026] Figure 3 This is a spheroidization rate rating chart for the ductile iron prepared in Example 3 of the present invention;

[0027] Figure 4 The spheroidization rate rating chart is shown for the ductile iron prepared in Comparative Example 1 of this invention.

[0028] Figure 5 The spheroidization rate rating chart is shown for the ductile iron prepared in Comparative Example 5 of this invention.

[0029] Figure 6 This is a rating chart of the spheroidization rate of the ductile iron prepared in Comparative Example 11 of this invention.

[0030] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0031] The technical solutions described below in conjunction with the embodiments will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] This invention provides a method for preparing high-strength and high-toughness ductile iron, comprising the following steps:

[0033] S1. Obtain raw materials and smelt them to obtain molten iron. During the smelting process, add ferroniobium and heat the molten iron to 1540~1610℃ and keep it at that temperature for 5~15 minutes.

[0034] This invention directly incorporates ferroniobium (FeNb60 alloy) during the smelting stage to achieve niobium alloying. The process is simple, requires no pre-ball milling, and is less costly. Heating the molten iron to 1540-1610℃ and holding it for 5-15 minutes allows the ferroniobium to fully dissolve, resulting in a uniform distribution of niobium within the molten iron. During subsequent solidification and eutectoid transformation, niobium combines with carbon to form nanoscale NbC particles, which are dispersed and precipitated in the pearlite matrix. By pinning dislocations and refining the interlamellar spacing of the pearlite, a strong precipitation strengthening effect is produced, significantly improving the material's strength, hardness, wear resistance, and high-temperature stability.

[0035] S2. The molten iron is subjected to desulfurization and deoxidation treatment, and the slag is removed before iron is discharged. The temperature of the discharged iron is 1480~1520℃.

[0036] The low-sulfur and low-oxygen state of the molten iron is the first prerequisite for niobium to fully exert its function. Excessive sulfur content will consume magnesium in the spheroidizing agent, affecting the spheroidizing effect; excessive oxygen content will lead to oxidative burning of niobium, reducing the effective utilization rate of niobium, and increasing oxide inclusions. This invention strictly controls the sulfur content to ≤0.02wt%, creating favorable metallurgical conditions for the full dissolution of niobium and the effective formation of niobium carbide.

[0037] S3. Add rare earth spheroidizing agent and primary inoculant to the molten iron after slag removal to obtain molten metal.

[0038] This invention strictly controls the residual magnesium content in the molten metal to be 0.035wt%~0.050wt%, and the residual rare earth content to be 0.010wt%~0.030wt%. By using a rare earth spheroidizing agent and precisely controlling the residual rare earth content, the deterioration of graphite morphology due to excessive rare earth is avoided. After spheroidization treatment, the mixture is allowed to stand for 2~3 minutes to allow inclusions to float fully, but without excessive cooling, to ensure the temperature window required for subsequent casting.

[0039] S4. The molten metal is poured, and a secondary inoculant is added during the pouring process. After cooling, the high-strength and high-toughness ductile iron is obtained.

[0040] During the casting and cooling stages, the supercooling of the molten iron was reduced by casting at a low temperature of 1360~1380℃, which promoted the large-scale dispersion and precipitation of NbC in the early stage of solidification. By accelerating the cooling of thick-walled parts with a wall thickness of ≥50mm (cooling rate ≥50℃ / min), the high-temperature coarsening of NbC was suppressed, so that it maintained its nanoscale size and was evenly distributed in the matrix, thereby maximizing the precipitation strengthening effect.

[0041] Fine-grained strengthening and second-phase strengthening are effective means to overcome the inverted relationship between strength and toughness. Studies have found that when the endogenous second-phase particles are small in size, well bonded to the matrix interface, and dispersed, they can both hinder dislocation movement and improve strength, and maintain a certain degree of plasticity through microcrack passivation or crack deflection mechanisms. Based on this, this invention proposes a method for preparing high-strength and high-toughness ductile iron. This method involves directly adding niobium-iron during the smelting stage to achieve niobium alloying, combined with low-sulfur and low-oxygen molten iron, wire feeding spheroidization treatment, precise control of rare earth spheroidizing agent residue, low-temperature casting, and accelerated cooling processes. The aim is to directly obtain a microstructure with fine and round graphite spheroids and a pearlitic matrix strengthening in the as-cast state, eliminating the need for heat treatment processes such as annealing. This meets the urgent need for high-strength and high-toughness ductile iron in automotive axle housings, while simultaneously achieving energy conservation, emission reduction, cost reduction, and efficiency improvement.

[0042] After a series of performance tests, the ductile iron designed in this invention can directly meet the target strength and toughness indicators in the as-cast state without undergoing additional heat treatment processes such as quenching and tempering (e.g., normalizing, annealing, or isothermal quenching). This heat-treatment-free characteristic has significant technical and economic advantages: First, eliminating the heat treatment process effectively reduces energy consumption and equipment investment per unit product, thereby reducing manufacturing costs; second, eliminating the process waiting time required for heat treatment helps shorten the overall production cycle and improve equipment utilization; third, it avoids defects such as oxidation, dimensional deformation, and even cracking that may be caused during high-temperature treatment, especially for large, complex, thin-walled castings such as bridge housings, which can significantly improve dimensional stability and reduce scrap rates; fourth, reducing heat treatment processes helps reduce carbon dioxide emissions, which is in line with the development direction of green casting. Based on the above advantages, this invention is particularly suitable for the large-scale industrial manufacturing of high-load structural components with stringent strength and toughness requirements, large production batches, and high cost sensitivity, such as automotive bridge housings, wind turbine hubs, and rail transit bogies.

[0043] The raw materials used in this embodiment of the invention are: Q10 pig iron, scrap steel, and recycled material, with a mass ratio of 3:1:1. Among them, Q10 pig iron contains elements such as C, Si, Mn, P, S, Ti, and Cr. Among them, P, Ti, and Cr exist in pig iron as impurities or trace elements, which are inherent components in the pig iron smelting process. Scrap steel contains elements such as Mn, Cr, Ni, Cu, and Sn. These elements come from the original steel grade composition of the scrap steel and dissolve into the molten iron during the smelting process. The recycled material is ductile iron recycled parts generated in the previous production process. Its composition covers all the elements of the final ductile iron and is reintroduced into the molten iron after being remelted.

[0044] The main sources of the various elements in the ductile iron prepared by this invention are as follows:

[0045] C: Inherent components in pig iron, the content of which is controlled by the raw material ratio during the smelting process;

[0046] Si: An inherent component of pig iron, also introduced by inoculants and spheroidizing agents;

[0047] Mn: A natural component in pig iron and scrap steel;

[0048] Cu: An inherent component in scrap steel;

[0049] Sn: An inherent component in scrap steel;

[0050] Mg: introduced by rare earth spheroidizing agents;

[0051] Ni: An inherent component in scrap steel;

[0052] Nb: Introduced by FeNb60 alloy (ferroniobium) added during the smelting stage;

[0053] RE: Rare earth spheroidizing agent introduced;

[0054] Ti: an inherent trace element in pig iron, and a trace impurity in FeNb60 alloy;

[0055] P: An inherent impurity element in pig iron and scrap steel;

[0056] S: Inherent components in pig iron;

[0057] Al: Introduced by the inoculant, FeNb60 alloy also contains Al impurities;

[0058] Cr: An inherent component of scrap steel;

[0059] B: Inherent components of pig iron.

[0060] In the embodiments of this invention, the rare earth content in the rare earth spheroidizing agent is 2wt%.

[0061] Example 1

[0062] A method for preparing high-strength and high-toughness ductile iron includes the following steps:

[0063] S1. Obtain raw materials and smelt them to obtain molten iron. During the smelting process, add 0.14% FeNb60 alloy of the total mass of the molten iron, heat the molten iron to 1540℃ and hold for 5 minutes.

[0064] S2. The molten iron is subjected to desulfurization and deoxidation treatment, and the molten iron is tapped after slag removal. The tapping temperature is 1500℃. The sulfur content in the molten iron after desulfurization and deoxidation treatment is 0.015wt%, and the oxygen content is 15ppm.

[0065] S3. A rare earth spheroidizing agent and a primary inoculant (silicon-barium inoculant) are added to the molten iron after slag removal using a cored wire feeding method to obtain a molten metal. The amount of rare earth spheroidizing agent added is 1% of the total mass of the molten iron, the amount of primary inoculant added is 0.21% of the total mass of the molten iron, the residual magnesium content in the molten metal is 0.042 wt%, the residual rare earth content is 0.014 wt%, and the mixture is allowed to stand for 2-3 minutes to allow the inclusions to float to the surface.

[0066] S4. The molten metal is poured at 1370℃. During the pouring process, 0.1% of secondary inoculant (silicon-barium inoculant) is added. For parts with a wall thickness ≥50mm, external chills are placed at the hot spots to control the cooling rate of the eutectoid transformation zone at 60℃ / min.

[0067] The chemical composition of the obtained ductile iron is as follows: C 3.55wt%, Si 2.70wt%, Mn 0.35wt%, Cu 0.60wt%, Sn 0.03wt%, Mg 0.036wt%, Ni 0.40wt%, Nb 0.08wt%, RE 0.012wt%, Ti 0.03wt%, Al 0.013wt%, P 0.02wt%, Cr 0.08wt%, B 0.0005wt%, S 0.012wt%, with the balance being Fe and unavoidable impurities.

[0068] Example 2

[0069] Differences from Example 1:

[0070] In step S1, the molten iron is heated to 1560°C and held at that temperature for 10 minutes;

[0071] In step S2, the iron tapping temperature is 1480℃, and the sulfur content in the molten iron after desulfurization and deoxidation treatment is 0.013wt% and the oxygen content is 13ppm.

[0072] In step S3, the amount of rare earth spheroidizing agent added is 1.2% of the total mass of the molten iron, the amount of primary inoculant added is 0.25% of the total mass of the molten iron, the residual magnesium content in the molten metal is 0.046 wt%, and the residual rare earth content is 0.02 wt%.

[0073] In step S4, the molten metal is poured at 1360°C, and 0.11% of a secondary inoculant is added during the pouring process. The cooling rate of the eutectoid transformation zone is 50°C / min.

[0074] The chemical composition of the obtained ductile iron is as follows: C 3.2wt%, Si 2.3wt%, Mn 0.1wt%, Cu 0.3wt%, Sn 0.03wt%, Mg 0.041wt%, Ni 0.3wt%, Nb 0.07wt%, RE 0.01wt%, Ti 0.02wt%, Al 0.017wt%, P 0.01wt%, Cr 0.04wt%, B 0.0002wt%, S 0.009wt%, with the balance being Fe and unavoidable impurities.

[0075] Example 3

[0076] Differences from Example 1:

[0077] In step S1, 0.17% of the total mass of the molten iron is added during the smelting process, and the molten iron is heated to 1580°C and held at that temperature for 15 minutes.

[0078] In step S2, the iron tapping temperature is 1520℃, and the sulfur content in the molten iron after desulfurization and deoxidation treatment is 0.01wt% and the oxygen content is 9ppm.

[0079] In step S3, the amount of rare earth spheroidizing agent added is 1.4% of the total mass of the molten iron, the amount of primary inoculant added is 0.26% of the total mass of the molten iron, the residual magnesium content in the molten metal is 0.044 wt%, and the residual rare earth content is 0.026 wt%.

[0080] In step S4, the molten metal is poured at 1380°C, and 0.13% of a secondary inoculant is added during the pouring process. The cooling rate of the eutectoid transformation zone is 80°C / min.

[0081] The chemical composition of the obtained ductile iron is as follows: C 3.8wt%, Si 3.5wt%, Mn 0.7wt%, Cu 0.9wt%, Sn 0.035wt%, Mg 0.038wt%, Ni 0.5wt%, Nb 0.09wt%, RE 0.023wt%, Ti 0.04wt%, Al 0.012wt%, P 0.012wt%, Cr 0.09wt%, B 0.0006wt%, S 0.007wt%, with the balance being Fe and unavoidable impurities.

[0082] Comparative Example 1

[0083] Differences from Example 1:

[0084] In step S1, niobium iron is not added.

[0085] The resulting ductile iron did not achieve niobium strengthening.

[0086] Comparative Example 2

[0087] Differences from Example 1:

[0088] In step S4, instead of using external chills or air cooling to accelerate cooling, the thick-walled sections are cooled naturally, with a cooling rate of 15°C / min in the eutectoid transformation zone.

[0089] Comparative Example 3

[0090] Differences from Example 1:

[0091] In step S1, the molten iron is heated to 1540°C and then held at that temperature for 2 minutes.

[0092] Comparative Example 4

[0093] Differences from Example 1:

[0094] In step S1, the molten iron is heated to 1480°C and held at that temperature for 5 minutes.

[0095] Comparative Example 5

[0096] Differences from Example 1:

[0097] In step S2, no desulfurization is performed, only deoxidation is performed, and the sulfur content in the molten iron is 0.028 wt%.

[0098] Comparative Example 6

[0099] Differences from Example 1:

[0100] In step S3, the mass fraction of magnesium in the molten metal is 0.065 wt%, and the mass fraction of rare earth elements is 0.045 wt%.

[0101] Comparative Example 7

[0102] The chemical composition of ductile iron is formulated according to the following mass percentages: C 3.6wt%, Si 2.10wt%, Mn 0.2wt%, Cu 0.60wt%, Sn 0.02wt%, P<0.05wt%, S<0.012wt%, with the balance being Fe and unavoidable impurities (excluding alloying elements such as Nb, RE, Ni, and Ti).

[0103] The preparation process is as follows:

[0104] S1. Weigh pig iron, scrap steel, recycled materials and carbonizer according to the above composition, and smelt them in a medium frequency induction furnace at a smelting temperature of 1500℃ to obtain molten iron.

[0105] S2. Desulfurize and deoxidize the molten iron. The sulfur content in the molten iron is 0.015wt%, and the oxygen content is ≤8ppm.

[0106] S3. After removing the slag from the molten iron, a rare earth spheroidizing agent is added using the cored wire feeding method for spheroidization treatment, and an inoculant is added at the same time to obtain molten metal.

[0107] S4. The molten metal is poured at 1370℃, and a secondary inoculant is added along with the flow. After pouring, it is naturally cooled to room temperature to obtain the as-cast ductile iron part.

[0108] Comparative Example 8

[0109] Differences from Example 1:

[0110] In step S1, the molten iron is heated to 1540°C and then kept at that temperature for 20 minutes.

[0111] Comparative Example 9

[0112] Differences from Example 1:

[0113] In step S2, the tapping temperature is 1450℃.

[0114] Comparative Example 10

[0115] Differences from Example 1:

[0116] In step S2, the tapping temperature is 1550℃.

[0117] Comparative Example 11

[0118] Differences from Example 1:

[0119] In step S3, the rare earth content in the added rare earth spheroidizing agent is 2.3 wt%.

[0120] Comparative Example 12

[0121] Differences from Example 1:

[0122] In step S3, the amount of rare earth spheroidizing agent added is 2.5 wt% of the total mass of the molten iron.

[0123] Comparative Example 13

[0124] Differences from Example 1:

[0125] In step S3, the amount of rare earth spheroidizing agent added is 0.8% of the total mass of the molten iron.

[0126] Comparative Example 14

[0127] Differences from Example 1:

[0128] In step S4, the temperature at which the molten metal is poured is 1340°C.

[0129] Comparative Example 15

[0130] Differences from Example 1:

[0131] In step S4, the temperature at which the molten metal is poured is 1400°C.

[0132] The products prepared in the examples and comparative examples were subjected to the following tests:

[0133] Mechanical property testing: The lower part of the cast Y-shaped test block was machined into a standard tensile specimen (dimensions: diameter d=10mm, original gauge length L0=50mm, parallel section length Lc=60mm). Tensile testing was performed using a universal testing machine at a tensile rate of 0.5mm / min to obtain tensile strength, yield strength and elongation data.

[0134] Hardness test: The hardness of the sample was tested using a Brinell hardness tester.

[0135] Metallographic observation: Metallographic specimens were prepared by taking samples from the broken end of the specimen and grinding them. The specimens were etched with 4% nitric acid alcohol solution. The spheroidization rate, graphite sphere size grade, number of graphite spheres, and volume fraction of pearlite and ferrite in the matrix were observed and counted using a metallographic microscope.

[0136] Microstructure and phase analysis: The tensile fracture morphology and pearlite lamellar spacing were observed using scanning electron microscopy (SEM); the phase composition was analyzed using X-ray diffraction (XRD).

[0137] The metallographic test results of the examples and comparative examples are shown in Table 1.

[0138] Table 1

[0139]

[0140] The mechanical property test results of the examples and comparative examples are shown in Table 2;

[0141] Table 2

[0142]

[0143] Calculate the spheroidization rate and spheroidization level according to the spheroidization rate rating chart in the attached diagram of the instruction manual, based on the national standard GB9441-2021. Figure 1 The image shows the spheroidization rate rating of the ductile iron prepared in Example 1 of this invention. The spheroidization rate is 95.6%, the spheroidization level is 2, and the pearlite content is 80%. Figure 2 The image shows the spheroidization rate rating of the ductile iron prepared in Example 2 of this invention. The spheroidization rate is 92.8%, the spheroidization level is 3, and the pearlite content is 72%. Figure 3 The image shows the spheroidization rate rating of the ductile iron prepared in Example 3 of this invention. The spheroidization rate is 97.2%, the spheroidization level is 2, and the pearlite content is 92%. Figure 4 The image shows the spheroidization rate rating of the ductile iron prepared in Comparative Example 1 of this invention. Its spheroidization rate is 86.5%, the spheroidization level is 4, and the pearlite content is 52%. Figure 5 The image shows the spheroidization rate rating of the ductile iron prepared in Comparative Example 5 of this invention. Its spheroidization rate is 78.5%, the spheroidization level is 5, and the pearlite content is 45%. Figure 6 The image shows the spheroidization rate rating of the ductile iron prepared in Comparative Example 11 of this invention. The spheroidization rate is 79.2%, the spheroidization level is 5, and the pearlite content is 48%.

[0144] On the one hand, niobium, added directly during the smelting stage, dissolves fully in the molten iron and reacts with carbon during subsequent solidification and eutectoid transformation to form nano-sized NbC particles. These particles are dispersed and precipitated within the pearlite matrix, generating a strong precipitation strengthening effect by pinning dislocations and refining the interlamellar spacing of the pearlite. This significantly improves the material's strength, hardness, wear resistance, and high-temperature stability. The refined and uniformly distributed pearlite structure helps maintain a certain level of plasticity while ensuring high strength. On the other hand, the use of cored wire feeding for spheroidization treatment results in high and stable magnesium absorption. Combined with rare earth spheroidizing agents and precisely controlled magnesium and rare earth residue windows (residual magnesium mass fraction 0.035wt%~0.050wt%, residual rare earth mass fraction 0.010wt%~0.030wt%), the deterioration of graphite morphology by excessive rare earth is avoided. Furthermore, low-temperature casting and accelerated cooling suppress high-temperature coarsening of NbC, maintaining its nano-sized dispersed distribution and maximizing the precipitation strengthening effect.

[0145] This invention achieves niobium alloying by directly adding ferroniobium during the smelting stage, resulting in a simpler and lower-cost process. By strictly controlling the low-sulfur and low-oxygen state of the original molten iron, favorable metallurgical conditions are created for the full dissolution of niobium and the effective formation of niobium carbide. The spheroidizing treatment uses a cored wire feeding method, resulting in high and stable magnesium absorption, and the spheroidizing process produces less smoke and dust, making it environmentally friendly. Combining low-temperature casting with accelerated cooling processes for thick-walled sections promotes the dispersed precipitation of carbides in the early stages of solidification and effectively inhibits their high-temperature coarsening, achieving a synergistic effect of graphite morphology control and matrix strengthening. The ductile iron prepared using this method possesses excellent comprehensive mechanical properties, combining high strength and high plasticity, making it suitable for high-load structural components in fields such as automotive axle housings, wind power generation, and rail transportation, where stringent requirements for strength and toughness are necessary.

[0146] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.

Claims

1. A method for preparing high-strength and high-toughness ductile iron for automotive axle housings, characterized in that, Includes the following steps: S1. Obtain raw materials and smelt them to obtain molten iron. During the smelting process, ferroniobium is added, and the amount of ferroniobium added is 0.17% of the total mass of the molten iron. The molten iron is heated to 1580°C and held for 15 minutes. S2. The molten iron is subjected to desulfurization and deoxidation treatment, and the molten iron is tapped after slag removal at a temperature of 1520℃. The molten iron after desulfurization and deoxidation treatment has a sulfur content of 0.01wt% and an oxygen content of 9ppm. S3. Add a rare earth spheroidizing agent and a primary inoculant to the molten iron after slag removal to obtain a molten metal; the rare earth spheroidizing agent and the primary inoculant are added using a cored wire feeding method; the amount of rare earth spheroidizing agent added is 1.4% of the total mass of the molten iron, the rare earth content in the rare earth spheroidizing agent is 2 wt%, the residual magnesium content in the molten metal is 0.044 wt%, and the residual rare earth content is 0.026 wt%; the amount of the primary inoculant added is 0.26% of the total mass of the molten iron. S4. The molten metal is poured, and a secondary inoculant is added during the pouring process. The amount of secondary inoculant added is 0.13% of the total mass of the molten iron. After cooling, the high-strength and high-toughness ductile iron is obtained. The pouring temperature of the molten metal is 1380℃. The cooling is specifically to accelerate the cooling of the thick-walled part when the ductile iron solidifies. The thick-walled part is the casting part with a wall thickness of 50mm or more. The accelerated cooling is to place an external chill at the hot spot or use air cooling to make the cooling rate of the eutectoid transformation zone 80℃ / min. The chemical composition of the ductile iron, by weight percentage, includes: C 3.8wt%, Si 3.5wt%, Mn 0.7wt%, Cu 0.9wt%, Sn 0.035wt%, Mg 0.038wt%, Ni 0.5wt%, Nb 0.09wt%, RE 0.023wt%, Ti 0.04wt%, Al 0.012wt%, P 0.012wt%, Cr 0.09wt%, B 0.0006wt%, S 0.007wt%, with the balance being Fe and unavoidable impurities; The ductile iron has a tensile strength of 735 MPa, a yield strength of 575 MPa, a hardness of 298 HB, and an elongation of 10.1%. The spheroidal graphite cast iron has a spheroidization rate of 97.2%, with 325 graphite spheres per mm. 2 The content of pearlite is 92%, and the content of ferrite is 8%.

2. The method for preparing high-strength and high-toughness ductile iron according to claim 1, characterized in that, In step S1, the raw materials include at least one of Q10 pig iron, scrap steel, and recycled materials.

3. The method for preparing high-strength and high-toughness ductile iron according to claim 1, characterized in that, In step S1, the niobium iron is an FeNb60 alloy.

4. The method for preparing high-strength and high-toughness ductile iron according to claim 1, characterized in that, In step S3, the primary inoculant includes barium silicon inoculant, ferrosilicon inoculant, or calcium silicon inoculant.

5. The method for preparing high-strength and high-toughness ductile iron according to claim 1, characterized in that, In step S4, the secondary inoculant includes barium silicon inoculant, ferrosilicon inoculant, or calcium silicon inoculant.

6. A high-strength and high-toughness ductile iron, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • As-cast sand casting niobium-contained high-strength high-toughness nodular cast iron material and preparing method thereof

    CN110129665A